Providing information support to the Policy Studies Program of the College of Public Administration, University of the Philippines - Lacson, Zenaida C., 1949-
1) Presentation of the aims and objectives of the Policy Studies Program of the U.S. College of Public Administration, with brief discussion of its components; curricular development, policy research, build-up of library collections, and faculty and staff development.
2) Utilization of library research in determining the nature, areas, and institutional development of policy sciences. The institutional development includes the identification of research institutes, university program both here and abroad, and publications believed to have made great contributions in the development of the field.
3) Identification of the tools necessary for the study of policy sciences such as dictionaries, encyclopedia, and thesauri.
4) Identification of the important sources for the study of policy sciences. These sources are grouped into primary, secondary, and tertiary sources. The primary sources include books, periodicals, and research reports. The secondary sources include bibliographies, catalogs, indexes, abstracts, and reviews. The tertiary sources include directories and yearbooks.
5) Provision of a selected and annotated body of literature on the general approaches within policy studies.
Building up the collections is one of the most important tasks of librarians, yet little attention has been given to this aspect of professional work. It is said that the role of the library in general, is to support the objectives of its mother institution and in particular, to provide information and literature support to a contemplated program of study.
In dealing with the problem, this paper adopted the following steps
Using the Policy Studies Program of the College of Public Administration, University of the Philippines as a model, this paper aims to find out exactly how to operationalize the practice of librarians in providing information and literature support to a contemplated program of study of an institution; to establish formal procedures and discover mechanics that could be applied to other disciplines in performing such tasks; and to provide a selected and annotated body of literature for the general approaches within policy studies, which includes both foreign and local materials.
Thesis (M.L.S)--University of the Philippines, Diliman
Typescript.
Keywords: Policy science--Bibliography.; University of the Philippines Manila. College of Public Administration. Policy Studies Program